Konsepsi Taklid Mazhab Syiah Imamiyah - Muhammad Zuhdi Zaini (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
For a long time, the term “taqlid” has carried a negative connotation, especially when accompanied by the word “blind”. However, in the religious thought tradition of Shia Islam, the term "taqlid" holds a neutral meaning and, in fact, becomes a necessity for its followers. This is a logical consequence of the belief in imamah or leadership, which is one of the fundamental teachings of Shia Islam. Following the opinions of a marja taklid (highest religious authority) is considered obligatory and binding. A Shia adherent who does not obey the religious rulings issued by a mujtahid (jurisconsult) they follow will have all their religious practices deemed invalid. They place scholars on par with other professions, such as doctors and engineers, whose opinions are followed by their clients.